A Comparative Study on Speaking Anxiety Level Between Male and Female Students at the VIIth Grade of Islamic Boarding School Ashhabul Yamin Lasi - Mardhatilla, Mardhatilla; Putri, Hilma Pami; Melani, Melyann; Safitri, Widya (Lembaga Yasin AlSys, 2023)
This research was conducted because of some problems related to speaking anxiety in male and female students in English learning. Some female students looked worried about being pointed out and there were a few students who were able to raise their hands to give opinions. Then, some female students showed anxiety when they became the center of attention. Third, some male students looked hesitant when they pronounced some words. Lastly, some male students felt more comfortable when giving opinions or answering teacher questions by using their first language rather than the English language. Because of these problems, the researcher intended to find out the significant difference on speaking anxiety level between male and female students, and to find out the dominant factor of speaking anxiety in male and female students at the VIIth grade of Islamic Boarding School Ashhabul Yamin Lasi. The research design was Ex Post Facto research. The data were collected by using 18 items of the FLSAS (Foreign Language Speaking Anxiety Scale) questionnaire that were adopted from Ozturk and Gurbuz 2014. There were three indicators of speaking anxiety; Communication Apprehension, Test Anxiety and Fear of Negative Evaluation. The levels of speaking anxiety were low anxiety, moderate anxiety, and high anxiety. The population of this research was all of the seventh grade students which consisted of 3 classes. The sample was 80 students that were selected by using total sampling technique. The research was conducted in February 2022 in Islamic boarding School Ashhabul Yamin Lasi. Then, by using the SPSS program, an independent sample t-test was used to compare speaking anxiety level between male and female students, and a descriptive statistic was used to reveal the dominant factor of speaking anxiety in male and female students. The first result of the research showed that there was a significant difference on speaking anxiety level between male and female students at the VIIth grade of Islamic Boarding School Ashhabul Yamin Lasi. The researcher found the t-obtained (3.484) was higher than T-table (1.990). It means that Ha was accepted and Ho was rejected. The level of speaking anxiety in female students was moderate anxiety and male students were low anxiety. The second results that were the dominant factor of speaking anxiety in male students was test anxiety (18.12%), where it is because of students’ perception about English language. Meanwhile, the dominant factor of speaking anxiety in female students was fear of negative evaluation (20.68%), where it is because of unpreparedness of students.